Effective preparation of low-melting solder materials for atom probe tomography - Charlotte Cui; Michael Tkadletz; Michael Reisinger; Peter Imrich; Walter Hartner; Roland Brunner (Scientific Reports)
Abstract Low-melting metal alloys have gained renewed attention for additive manufacturing, energy storage and microelectronics. However, micro- and nanostructure characterisation demands highly sophisticated sample preparation. Here, we optimise the Ga-FIB preparation of atom probe tomography (APT) specimens for low melting SAC305 solder materials utilising different FESEM/FIB stage temperatures. We study the effects of FESEM/FIB stage temperature on the specimen milling behaviour during Ga-FIB preparation and compare the extent of Ga implantation and precipitate coarsening during the preparation utilising energy dispersive X-ray spectroscopy and APT. We show that cooling the sample to −60 °C during FIB milling utilising a Peltier cooling stage improves the behaviour of the specimen during the final low-keV milling step significantly. We conclude that performing all Ga-FIB-sample interactions at −60 °C with a Pt-protection layer allows for effective and reproducible APT specimen preparation for low-melting alloys, such as SAC305.